Blockchain-Based Electronic Voting Protocol - Clement Chan Zheng Wei; Chuah Chai Wen (Society of Visual Informatics, 2018)
Current electronic voting protocol require a centralized system to control the whole procedure from ballot inputs to result outputs and election monitoring. Meanwhile, blockchain technology provide a decentralized system which open across the whole network of untrusted participants. Applying blockchain technology into electronic voting protocol through a proper architecture can instil characteristic such as data confidentiality, data integrity and data authenticity. In this paper, we going to discuss a proposed method on how to leverage the advantages from blockchain into electronic voting protocol. This blockchain-based electronic voting protocol promise to provide a secure electronic election process given the proposed system works. We implement a protocol using blockchain to turn election protocol into an automated control system without relying any single point of entity. Lastly, we discuss the characteristics of our proposed blockchain-based electronic voting protocol in this paper. However, there are also emerging challenges and limitations awaiting to overcome. This paper gives a comprehensive overview of our proposed protocol.